2017
DOI: 10.5194/tc-11-2345-2017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the synoptic regime on stable water isotopes in precipitation at Dome C, East Antarctica

Abstract: Abstract. The correct derivation of paleotemperatures from ice cores requires exact knowledge of all processes involved before and after the deposition of snow and the subsequent formation of ice. At the Antarctic deep ice core drilling site Dome C, a unique data set of daily precipitation amount, type, and stable water isotope ratios is available that enables us to study in detail atmospheric processes that influence the stable water isotope ratio of precipitation. Meteorological data from both automatic weat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Fernandoy et al, 2018;Bertler et al, 2018;Schlosser et al, 2004;Dittmann et al, 2016). While distillation processes are expected theoretically to relate condensation temperature with precipitation isotopic composition, a number of deposition processes can distort this relationship: changes in moisture sources (Stenni et al, 2016), intermittency or seasonality of precipitation (Sime et al, 2008), boundary layer processes affecting the links between condensation and surface air temperature (Krinner et al, 2008), and several post-deposition processes, such as the effects of winds (Eisen et al, 2008), snow-air exchanges (Casado et al, 2016;Ritter et al, 2016), and diffusion processes in snow and ice (e.g. Johnsen, 1977).…”
Section: Climatic Interpretation Of Water Stable Isotope Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandoy et al, 2018;Bertler et al, 2018;Schlosser et al, 2004;Dittmann et al, 2016). While distillation processes are expected theoretically to relate condensation temperature with precipitation isotopic composition, a number of deposition processes can distort this relationship: changes in moisture sources (Stenni et al, 2016), intermittency or seasonality of precipitation (Sime et al, 2008), boundary layer processes affecting the links between condensation and surface air temperature (Krinner et al, 2008), and several post-deposition processes, such as the effects of winds (Eisen et al, 2008), snow-air exchanges (Casado et al, 2016;Ritter et al, 2016), and diffusion processes in snow and ice (e.g. Johnsen, 1977).…”
Section: Climatic Interpretation Of Water Stable Isotope Recordsmentioning
confidence: 99%
“…Delmotte et al, 2000). These features have been explored through the identification of back-trajectory clusters and their relationship with δ 18 Od-excess relationships, including phase lags (Markle et al, 2012;Caiazzo et al, 2016;Schlosser et al, 2017).…”
Section: Climatic Interpretation Of Water Stable Isotope Recordsmentioning
confidence: 99%
“…The ocean surface boundary conditions (sea ice included) are also prescribed based on ERA-40 and ERA-Interim data. Isotope values of ocean surface isotopic composition are based on a compilation of observational data (Schmidt et al, 2007). The simulation was performed at a T106 resolution (which corresponds to a mean horizontal grid resolution of approx.…”
Section: Echam5-wiso Model and Simulationmentioning
confidence: 99%
“…One study used climate projections in response to increased atmospheric CO 2 concentration to explore isotope-temperature relationships in a world warmer than today and suggested a changing temporal isotope-temperature relationship due to changing covariance between temperature and precipitation (Sime et al, 2009). Several observational and modelling studies have also evidenced different isotope-temperature relationships between the spatial relationship and those calculated at the seasonal (Morgan and van Ommen, 1997) or inter-annual scale (Schmidt et al, 2007).…”
mentioning
confidence: 99%
“…The impact of the wind in both methods cannot be removed entirely [17,46]. Other ablation processes show little effect on the evaluation of high snow accumulation events at synoptic timescales in Antarctica [13,38,39]. Previous studies have suggested that high accumulation events identified by a certain threshold are induced by precipitation at a synoptic timescale, and in situ measurements could be used to assess the performance of precipitation in reanalyses [8,13,39].…”
Section: Introductionmentioning
confidence: 99%